2020
DOI: 10.7150/ijms.41454
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of Tolvaptan to patients with decompensated cirrhosis

Abstract: Aim: Tolvaptan, an oral vasopressin-2 antagonist, sometimes improves hepatic edema including ascites in patients with decompensated cirrhosis. In this study, we examined the effectiveness and survival advantage in patients with the long-term administration of tolvaptan. Methods: A total of 115 patients with refractory ascites who were treated with tolvaptan were retrospectively analyzed based on their clinical records. Patients with a decrease in body weight of ≥1.5 kg from the baseline on day 7 were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This difference, or other unknown factors, might affect the clinical course after tolvaptan administration. Several studies have shown no impact of the tolvaptan response on the survival, as in our present study 31,32 . Given that large‐scale studies have shown significance, we must include more patients in subsequent studies.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This difference, or other unknown factors, might affect the clinical course after tolvaptan administration. Several studies have shown no impact of the tolvaptan response on the survival, as in our present study 31,32 . Given that large‐scale studies have shown significance, we must include more patients in subsequent studies.…”
Section: Discussionmentioning
confidence: 59%
“…Several studies have shown no impact of the tolvaptan response on the survival, as in our present study. 31,32 Given that large-scale studies have shown significance, we must include more patients in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, post hoc analyses did identify the class of patients who had an improved outcome with tolvaptan [ 89 ]. In liver cirrhosis, tolvaptan may improve long-term survival if the therapeutic response is sustained in Japanese patients [ 38 ], but other studies did not observe this better outcome, and EASL does not recommend its use for long term [ 1 ], whereas the Japan Society of Hepatology is more in favor [ 94 ]. More studies are therefore needed to better delineate the long-term use of tolvaptan.…”
Section: Disturbed Water Balancementioning
confidence: 99%
“…Several studies have shown that the administration of tolvaptan had no effect on survival [57,80,81]. These studies showed prognostic factors, such as complications with HCC and low fractional excretion of sodium (FENa) [57], complications with HCC and Child-…”
Section: Long-term Survival After Tolvaptan Administrationmentioning
confidence: 99%
“…Several studies have shown that the administration of tolvaptan had no effect on survival [ 57 , 80 , 81 ]. These studies showed prognostic factors, such as complications with HCC and low fractional excretion of sodium (FENa) [ 57 ], complications with HCC and Child-Pugh class C [ 80 ], and a rapid and early decrease in a bioimpedance analysis (defined by intracellular water at 6 h after the first dose of tolvaptan) [ 81 ]. These factors are also convincing.…”
Section: Management Of Ascitesmentioning
confidence: 99%